2012
DOI: 10.1037/a0027545
|View full text |Cite
|
Sign up to set email alerts
|

Mnemonic strategy training improves memory for object location associations in both healthy elderly and patients with amnestic mild cognitive impairment: A randomized, single-blind study.

Abstract: Objectives To evaluate the efficacy of mnemonic strategy training versus a matched-exposure control condition and also to examine the relationship between training-related gains, neuropsychological abilities, and medial temporal lobe volumetrics in patients with amnestic mild cognitive impairment (aMCI) and age-matched healthy controls. Methods Twenty-three of 45 screened healthy controls and 29 of 42 screened aMCI were randomized to mnemonic strategy or matched-exposure groups. Groups were run in parallel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 59 publications
7
95
0
Order By: Relevance
“…The third problem with using cutoff scores for cognitive rehabilitation research is that they fail to recognize the (Hampstead, Sathian, Phillips, Amaraneni, Delaune, & Stringer, 2012). Our data suggest that training is appropriate for those with ''early'' MCI whereas improvement following mere repeated exposure (without strategy use) was unrelated to any cognitive or volumetric variable, suggesting it is appropriate for any stage of MCI.…”
Section: Methodological Challenge 1: Diagnostic Criteriamentioning
confidence: 84%
“…The third problem with using cutoff scores for cognitive rehabilitation research is that they fail to recognize the (Hampstead, Sathian, Phillips, Amaraneni, Delaune, & Stringer, 2012). Our data suggest that training is appropriate for those with ''early'' MCI whereas improvement following mere repeated exposure (without strategy use) was unrelated to any cognitive or volumetric variable, suggesting it is appropriate for any stage of MCI.…”
Section: Methodological Challenge 1: Diagnostic Criteriamentioning
confidence: 84%
“…Cognitive training interventions based on repetitive practice on cognitive processes have been effective in improving the trained process but not so much for other untrained cognitive functions (Ball et al, , 2007Hampstead et al, 2012;Mozolic et al, 2011). Some clinical trials, however, have shown transfer to other domains different than that of the trained exercises (Cheng et al, 2012;Mahncke et al, 2006;Oswald et al, 2006;Richmond et al, 2011;Willis et al, 2006).…”
Section: Computerized Brain Training In Agingmentioning
confidence: 96%
“…A recent review outlined the main characteristics of cognitive rehabilitation versus cognitive training. Other researchers refer to this set of interventions based on mental stimulation as brain training (Buitenweg et al, 2012), cognitive exercise (Gates and Valenzuela, 2010) or cognitive rehabilitation (Hampstead et al, 2008(Hampstead et al, , 2012Stuss et al, 2007;Winocur et al, 2007). In our technological society, computer-based training programs and video games have attracted researchers' attention as possible tools for improving and/or maintaining perceptual and cognitive functions in older adults.…”
Section: Cognitive Training Approachesmentioning
confidence: 98%
See 1 more Smart Citation
“…Group teaching of visual memory strategies have been successful in helping people recall placement of objects in their homes. 67 Increasingly, group efforts are being implemented, including a two-week intensive program offered through the Mayo clinic, as well as "Cogs Clubs" and "Memory Cafes," both grassroots movements that meet standards for clinically relevant interventions. 68 There is increasing literature on the benefits of socializing in groups and interpersonal learning as a mechanism of change.…”
Section: Original Research and Contributionsmentioning
confidence: 99%